The LOB-like transcription factor Mt LBD1 controls Medicago truncatula root architecture under salt stress - Ariel, Federico Damian (2010)
Lateral root (LR) formation and emergence are influenced by the environment and determines the architecture of the root system in the soil. Whereas auxins appear as the main hormone controlling LR initiation, patterning and emergence, abscisic acid (ABA) is the key hormone mediating the effect of the environment on root architecture. Hormone signaling act through transcription factors (TFs) and the Medicago truncatula LOB-like TF LBD1 was shown to be auxin-inducible but repressed by the HD-Zip I TF MtHB1 in response to salt stress and ABA during LR formation. Here, we demonstrate that the constitutive expression of Mt LBD1 in Medicago roots alters their global architecture when the plant is subjected to salt stress. Hence, LBD1 may control the final form of the root system in the soil environment.